Evaluation of the spatial distribution of Fasciola hepatica and Fasciola gigantica using geographical information system (GIS) in the Nile River Basin, Ethiopia - Asrat, M.; Peden, Donald G.; Jobre, Y.; Abebe, G.; Gideyelew, T. (2007)
The purpose of this paper is to describe how Geographic Information Systems (GIS) can be used to assist reviews to suggest complex information simply, via a spatial depiction. Fasciolosis risk maps are a convenient tool for developing targeted and cost-effective interventions with disease control personnel. A GIS risk modeling approach for the snail-borne disease caused by Fasciola species was developed using a combination of altitude, temperature and land slope to estimate potential spatial distribution of the parasite. This enabled mapping the spatial clustering of irregular events and identification of spatial risk areas, which could indicate potential endemic areas for fasciolosis. The model indicates highly, moderately, least and non- risk prone areas for F. hepatica cluster in the central and southern part of Nile watershed. In contrast to F. hepatica, the results showed that F. gigantica has the highest density in the western part of Nile watershed. The risk gradually declines with decreasing elevation for F. hepatica and increasing elevation for F. gigantica. There is almost no risk of F. hepatica and for F. gigantica in 12.34% and 19.44% of the Nile River Basin area, respectively. The study shows how GIS can be used to create an improved basis for strategic control of the disease.